Mineral Fibres - Pereira, Lola (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In the last decades, there has been increasing interest in Naturally Occurring Asbestos (NOA) and asbestos containing materials (ACMs) as a source of possible environmental risk. A crucial theme of interest related to environmental pollution is the enhanced mobilization of asbestos minerals affecting soils and rocks due to human activities (e.g., road construction, mining activity) in comparison with natural weathering processes. The volume has aimed to gather contributions and to compare results derived from various experiences of research groups regarding NOA minerals as a source of possible environmental risks for population. Case studies from various geological contexts are presented. Moreover, contributions presenting novel and classical approaches for ACM inertization and recycling, together with possible solutions for reducing asbestos exposure, has been also presented.